2011
DOI: 10.2134/jeq2010.0209
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Antibiotic Resistance Genes in Manure, Biosolids, and Fertilized Soil

Abstract: Increasing antibiotic resistance genes in the environment may pose a threat to public health. In this study, tetracycline and sulfonamide resistance genes (Tet-W, Tet-O, and Sul-I) were quantified in 24 manure samples from three farms and 18 biosolids samples from seven different wastewater treatment plants using quantitative polymerase chain reaction methods. Concentrations of Tet-W and Tet-O genes were observed to be significantly higher (p < 0.05) in manure than in biosolids samples. The background soil sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
95
3
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(110 citation statements)
references
References 44 publications
10
95
3
2
Order By: Relevance
“…Residual solid materials recovered from municipal wastewater treatment systems are rich in microorganisms and a diversity of antibiotic resistance genes (18,21). No more viable enteric bacteria were detected in soil or on vegetables at harvest from plots receiving either biosolids or untreated sewage sludge than in control plots that were fertilized inorganically only (see Tables S4 and S5 in the supplemental material).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Residual solid materials recovered from municipal wastewater treatment systems are rich in microorganisms and a diversity of antibiotic resistance genes (18,21). No more viable enteric bacteria were detected in soil or on vegetables at harvest from plots receiving either biosolids or untreated sewage sludge than in control plots that were fertilized inorganically only (see Tables S4 and S5 in the supplemental material).…”
Section: Discussionmentioning
confidence: 99%
“…Biosolids entrain sorbed antibiotics, including various fluoroquinolones, macrolides, and tetracycline, into soil (17). Soils fertilized with biosolids are enriched with antibiotic resistance genes and with integrons associated with genetic mobility (18,19). There is a risk, therefore, that human consumption of crops grown in ground fertilized with human waste will increase exposure to antibiotic-resistant bacteria and genetic determinants.…”
mentioning
confidence: 99%
“…Anthropogenic activities such as RWI and other agricultural practices may contribute to expansion of soil antibiotic resistance (Munir and Xagoraraki, 2011;Cytryn, 2013), and potentially threaten human health through transfer of ARGs and ARB into human-associated pathogens (Forsberg et al, 2012) and food chain (Marti et al, 2013;Wang et al, 2015a). In this study, the numbers and fold changes of the detected ARGs were found to be significantly greater in urban parks with RWI than those without RWI, suggesting that RWI could enhance the diversity and enrichment of soil ARGs.…”
Section: Impacts Of Rwi On the Patterns Of Args In Urban Park Soilsmentioning
confidence: 58%
“…Third, higher diversity in plant species may create an increased bacterial diversity. Moreover, previous studies found that there were more disturbances in residential soils (Mendes et al, 2011;Munir and Xagoraraki, 2011;Liu et al, 2012).…”
Section: Effect Of Different Land-use On Bacterial Community Compositionmentioning
confidence: 97%